2012
DOI: 10.3389/fphar.2012.00203
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Eosinophil Adhesion and Accumulation in Allergic Conjunctivitis

Abstract: Considerable evidence indicates that eosinophils are important effectors of ocular allergy. Increased worldwide prevalence of allergic eye pathologies has stimulated the identification of novel drug targets, including eosinophils and adhesion molecules. Accumulation of eosinophils in the eye is a key event in the onset and maintenance of allergic inflammation and is mediated by different adhesion molecules. Antihistamines with multiple mechanisms of action can be effective during the early and late phases of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Herein we describe the use of the Amo α/β‐dipeptide scaffold for the design of stable peptidomimetic antagonists of the integrin α4β1, or very late activation antigen‐4 (VLA‐4), a heterodimeric cell‐surface receptor expressed on lymphocytes, monocytes, eosinophils, basophils, macrophages. The integrin α4β1 has been suggested to be involved in inflammatory processes associated with the sustained recruitment of these cells, and targeted by monoclonal α4 integrin antibodies and small‐molecule antagonists, which may find applications as anti‐inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we describe the use of the Amo α/β‐dipeptide scaffold for the design of stable peptidomimetic antagonists of the integrin α4β1, or very late activation antigen‐4 (VLA‐4), a heterodimeric cell‐surface receptor expressed on lymphocytes, monocytes, eosinophils, basophils, macrophages. The integrin α4β1 has been suggested to be involved in inflammatory processes associated with the sustained recruitment of these cells, and targeted by monoclonal α4 integrin antibodies and small‐molecule antagonists, which may find applications as anti‐inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…The contained ginsenosides can exert a controlled glucocorticoid-like effect. 29,30 Safety issues associated with long-term administration of KRG should be considered. A multicenter, double-blind, randomized, placebo-controlled trial, involving 100 patients and conducted over a 24-week period, revealed no significant differences in adverse events between KRG and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…As CAPT is an in vivo diagnosis procedure, the application of the allergen is not appropriate for pregnant or lactating women, as well as patients affected by uncontrolled diseases, particularly uncontrolled asthma, and severe systemic diseases such as autoimmune, heart and vascular diseases (e.g. uncontrolled hypertension, in case adrenaline is needed to treat an adverse event), hyperthyroidism, severe liver or renal insufficiencies and ongoing malignancies . Conjunctival allergen provocation test is not recommended in patients suspected of allergy to drugs used for the CAPT procedure (e.g.…”
Section: Indications and Contraindications Of The Captmentioning
confidence: 99%